Prevalence of Raynaud's phenomenon in Great Britain and its relation to hand transmitted vibration: A national postal survey - Palmer, K; Syddall, H; Pannett, B; Cooper, C; Coggon, D; Griffin, M (2000)
Objectives - To assess the prevalence of Raynaud's phenomenon in the general population of Great Britain and to estimate the proportion and number of cases attributable to hand transmitted vibration (HTV). Methods - A questionnaire was posted to a random sample of 22 194 adults of working age. Information was collected on the lifetime prevalence of finger blanching, smoking habits, and occupational and leisure time exposures to HTV. Associations with risk factors were explored by logistic regression, with odds ratios converted into prevalence ratios (PRs). Results - Among the 12 907 respondents, 1835 (14.2%) reported finger blanching at some time, including 1529 (11.8%) in whom symptoms were induced by cold, and 597 (4.6%) in whom the blanched area was also clearly demarcated. Prevalences were higher in women than men. Around one fifth of cases (2% of respondents) had consulted a doctor about their symptoms. By comparison with men who had never been exposed to HTV, the PR for cold induced blanching in those exposed only at work was 2.0 (95% CI 1.7 to 2.3), and in men exposed both at work and in leisure it was 2.5 (95% CI 2.1 to 3.1). Higher risks were found in men who consulted a doctor about cold induced blanching, among whom 37.6% of cases were estimated to arise from exposure to HTV. The estimated number of cases attributable to HTV nationally was 222 000 in men who reported extensive blanching (blanching affecting at least eight of the digits or 15 phalanges). Similar patterns of risk were found in women, but the attributable proportion was much lower (5.3% in cases consulting a doctor). Conclusions - Raynaud's phenomenon is common in the general population. Many cases are attributable to HTV, especially in men, emphasising the public health importance of this common occupational hazard.